STUDI ETNOBOTANI TANAMAN OBAT TRADISIONAL PADA MASYARAKAT DI DESA ORAHILI KECAMATAN SIROMBU KABUPATEN NIAS BARAT - Damai Yanti Daeli (TUNAS : Jurnal Pendidikan Biologi, 2023)
This study aims to determine the use of medicinal plants that exist around the community as one of the traditions of Community Medicine in Orahili Village, Sirombu District, West Nias Regency and to determine how to process traditional medicinal plants used by the people of Orahili Village, Sirombu District, West Nias Regency. This study is a type of qualitative research with the number of informants as many as 10 (ten) people. Data collection techniques with observation, interviews and documentation. Data analysis technique uses a method that consists of three stages, namely data reduction, data display, and conclusion. The conclusion in this study is, the use of traditional medicinal plants in the village of Orahili is a tradition that has been passed down from generation to generation by previous parents, pengelohana medicinal plants in the village of Orahili done by boiling, pounded, evaporated, steamed, pounded, milled, sliced, shredded and kneaded in water. Suggestions in this study are (1) in utilizing medicinal plants, is expected to be maintained and taught to the next generation. (2) it should be determined in the processing of medicinal plants consumed by Orahili villagers how many doses can be used in preventing and treating diseases. (3) follow-up research is necessary, meaning that it is expected that the next researcher to be able to examine more things related to the utilization of traditional medicinal plants, especially with the local wisdom of a region.